Malaysia's national ecotourism plan from a semiotic perspective - Siow, May Ling; Ramachandran, Sridar; Shuib, Ahmad; Mohammad Afandi, Syamsul Herman (Forestry Department Peninsular Malaysia, 2014)
The purpose of the study is to reveal the semiotic meaning of The National Ecotourism Plan Malaysia. Semiotic analysis approach is used to achieve this objective. This paper adapts the 4-phase research process of design principle, data elicitation, data analysis and knowledge interest. The structure of meaning from textual angles is reviewed prior to applying the semiotic analysis approach on the text corpus of the plan. The finding of this paper discusses the underlying structure of meaning of the plan from the perspective of a policy analyst where 10 themes and 31 textual symbols were established.